THE BLOCKCHAIN-BASED ON E-VOTING IN THE LOCAL ELECTIONS SYSTEM: AN EFFORT TO REALIZE E-DEMOCRACY - Mohammad Syaiful Aris; Dita Elvia Kusuma Putri; Gio Arjuna Putra; Xavier Nugraha (Jurnal Pembaharuan Hukum, 2023)
E-voting in post-conflict local elections is still a long debate. One of the reasons is related to the security problem e-voting. Over time, system blockchain born which is known unhackable. Therefore, will analyze, first, urgency using e-voting in post-conflict local election system and secondly the formulation use of blockchain-based e-voting in the post-conflict local election system. The method research is legal research with statute approach, conceptual approach, and case approach. As for the results of the study: first, urgency using blockchain in regional head election system, because there are still many problems, namely: 1) Multiple voter data which results in voters being able to vote more than one time, 2) There are still ballots that have been voted, due irresponsible persons, 3) Distribution of ballot boxes and ballots have problems both before and after voting, and 4) Many post-conflict local election officers died and got sick due to fatigue while on duty, and secondly, the formulation use blockchain in electronic-based regional head election system, must considered: 1) review readiness of districts/cities, 2) Making rules with stakeholders, 3) Resource training humans, 4) Socialization to the community, 5) The implementation is carried out systematically tiered, 6) Implement pilot project before implemented.